“They Say the Water Is Perfectly Safe but…”: A Mixed‐Methods Participatory Study of Factors Influencing Trust in Tap Water Safety in a Great Lakes City - Colleen M. O’Brien; Vidya Venkataramanan; Clare Tallon Ruen; Erin McCotter; Anika Mittu; Revika Singh; Liliana Hernandez Gonzalez; Aaron I. Packman; William M. Miller; Sera L. Young (Community Science)
AbstractThe majority of households in high‐income countries have access to safely managed drinking water, but a significant number do not trust or use their tap water. Much remains unknown about the perceptions and behaviors of millions of people who opt to not drink tap water that meets national guidelines. Given that tap water avoidance is associated with myriad adversities and bottled water generates enormous amounts of waste, information about the drivers of trust in tap water is critical. Therefore, we investigated drinking water perceptions and behaviors in 2020–21 in Evanston, Illinois, a mid‐size city on Lake Michigan whose water quality meets or exceeds federal guidelines. In collaboration with a local environmental organization and a university, we conducted community‐based participatory research that included surveys (n = 756) and in‐depth interviews (n = 52) with a convenience sample of residents. Most (92.6%) respondents reported primarily consuming tap water. 81.2% of survey respondents (n = 749) thought their tap water was safer than or as safe as bottled water. Those who drank primarily bottled water (7.4%) were more likely to identify as Black, Indigenous, People of Color (BIPOC) or unhoused. BIPOC individuals had 3.4 times the odds of distrusting tap water than white respondents and men were 44% less likely to distrust tap water than women. Adverse experiences with water and low trust in government were also associated with lower trust in tap water safety. These findings suggest that outreach be targeted toward these groups to ensure widespread access to safe and trusted tap water.